2009
DOI: 10.1088/0004-637x/708/1/675
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of the Dynamics and Particle Acceleration of Knots in the Jet of Centaurus A

Abstract: We present new and archival multi-frequency radio and X-ray data for Centaurus A obtained over almost 20 years at the VLA and with Chandra, with which we measure the X-ray and radio spectral indices of jet knots, flux density variations in the jet knots, polarization variations, and proper motions. We compare the observed properties with current knot formation models and particle acceleration mechanisms. We rule out impulsive particle acceleration as a formation mechanism for all of the knots as we detect the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 51 publications
3
91
0
1
Order By: Relevance
“…Clarke et al (1992) found no evidence for internal depolarisation, so that only upper limits on the thermal electron densities can be inferred. For the knots for which we have sufficient constraints, A1A, A1B and A1C, using equipartition fields of 693, 323 and 763 μG (Goodger et al 2010), this gives upper limits of n e,th ∼ 3 × 10 −2 , ∼6 × 10 −3 and ∼8 × 10 −2 cm −3 , respectively. These are well above the densities that we estimate from entrainment.…”
Section: Constraints On Energy Density and Magnetic Fieldsmentioning
confidence: 99%
“…Clarke et al (1992) found no evidence for internal depolarisation, so that only upper limits on the thermal electron densities can be inferred. For the knots for which we have sufficient constraints, A1A, A1B and A1C, using equipartition fields of 693, 323 and 763 μG (Goodger et al 2010), this gives upper limits of n e,th ∼ 3 × 10 −2 , ∼6 × 10 −3 and ∼8 × 10 −2 cm −3 , respectively. These are well above the densities that we estimate from entrainment.…”
Section: Constraints On Energy Density and Magnetic Fieldsmentioning
confidence: 99%
“…These observations have allowed unprecedented insight into the X-ray jets (Hardcastle et al 2007;Worrall et al 2008;Goodger et al 2010), radio-lobe shock (Croston et al 2009), extended gaseous emission , and work on the XB, particularly in relation to globular clusters (Voss et al 2009, see also Woodley et al 2008 using pre-VLP data).…”
Section: Ngc 5128mentioning
confidence: 99%
“…This is much like the Centaurus A jet, but there the case for X-ray synchrotron emission is strong (e.g. Goodger et al 2010). The main issue for Cygnus A is that an active power source is required to maintain the population of highly relativistic electrons.…”
Section: X-ray Jetmentioning
confidence: 99%